Case Report: A novel CXCR4 variant (p.S341Y) in a family with a pathogenic NFKB1 variant and variable clinical manifestations - Yilmaz, Melis; Zmajkovicova, Katarina; Miller, Rahim Z.; Blair, Grace; Ellison, Maryssa; Ujhazi, Boglarka; Lopez, Maria Chitty; Dasso, Joseph F.; Bledsoe, Jacob R.; Csomos, Krisztian; Maierhofer, Barbara; Badarau, Adriana; et al. (Frontiers in Immunology, 2025)
WHIM syndrome is typically caused by C-terminal gain-of-function variants in CXCR4, yet clinical heterogeneity suggests additional genetic modifiers. We investigated a family in which the 22-year-old proband harbored two heterozygous variants: a novel CXCR4 missense variant, c.1022C>A (p.S341Y), and a frameshift variant in NFKB1, c.980dup (p.A328Sfs*12). Functionally, CXCR4 p.S341Y substitution - located two residues upstream of the known pathogenic p.E343K variant - increased CXCL12-induced chemotaxis and ERK/AKT signaling while minimally affecting receptor internalization, supporting a partial CXCR4 gain-of-function. The CXCR4 variant co-segregated with mild neutropenia, recurrent respiratory infections, and cutaneous warts in the paternal lineage. In contrast, the maternal NFKB1 variant was associated with agammaglobulinemia and autoimmunity. Their co-inheritance in the proband resulted in a blended WHIM/CVID phenotype characterized by myelokathexis, B-cell maturation arrest and T-cell dysregulation. This case expands the phenotypic spectrum of CXCR4 variants and highlights how multilocus inheritance can obscure classical diagnostic boundaries and guide individualized therapy.